2015
DOI: 10.1039/c5dt01339a
|View full text |Cite
|
Sign up to set email alerts
|

Maleimide fused boron–fluorine complexes: synthesis, photophysical and electrochemical properties

Abstract: Novel boron fluorine complex molecules were designed and synthesized using the maleimide core moiety. Significant features such as a large Stoke shift, high quantum yield, and long range absorption and emission wavelengths were observed for these molecules. The lower LUMO level of these molecules indicates their potential application as electron transport materials. The optical band gap was calculated and compared by using UV-absorption edge, density functional theory and electrochemical studies, revealing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Rather than a single narrow band (at ≈ 500 nm) typical of BODIPY dyes, the optical absorption spectrum of (pdp)BF 2 presents two broad envelopes of intense bands with maxima at ≈ 375 and ≈ 445 nm (Figure and Table S4). Notably, the significant blue shift and broader bands of this absorption profile resemble those reported for other BODIPY analogs featuring a carbonyl group at one of the α‐pyrrolic positions …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Rather than a single narrow band (at ≈ 500 nm) typical of BODIPY dyes, the optical absorption spectrum of (pdp)BF 2 presents two broad envelopes of intense bands with maxima at ≈ 375 and ≈ 445 nm (Figure and Table S4). Notably, the significant blue shift and broader bands of this absorption profile resemble those reported for other BODIPY analogs featuring a carbonyl group at one of the α‐pyrrolic positions …”
Section: Resultssupporting
confidence: 68%
“…[31] Whereas the Stokes shifts show negligible solvent effects, the quantum yields exhibit a general (albeit not linear) increase with increasing solvent polarity (Table S4). As previously noted for other cyan-emitting BODIPYs featuring α-carbonyl groups, [26][27][28][29] the emission spectra do not mirror the absorption ones thus indicating marked alterations of the potential energy surfaces of the excited states (relative to the ground state) when compared to classic BODIPY dyes.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Although the synthesis of compounds 1-3 and their derivatives have been previously documented, [19][20][21][22][23][24] the development of reaction conditions with good to excellent yields for each step remained a challenge in our study. Compound 1 was obtained using 2-phenylacetic acid and 2-bromo-1-phenylethanone as the starting materials.…”
Section: Resultsmentioning
confidence: 99%
“…51 In these cases, low to moderate synthetic yields were also reported. [52][53][54] In order to optimize this reaction, LiHMDS was trialled as a base based on a previous study 55 and higher yields were observed.…”
Section: Design and Synthesismentioning
confidence: 99%